STRATEGI BERTAHANNYA WARUNG KELONTONG DALAM GEMPURAN MARKET MODERN - Yohanna Meilani Putri; Rica Agatha; Reefadhinta Novta Amelia (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The development of the times has brought the transition of the traditional era to modern. The existence of grocery stalls is synonymous with small businesses that provide consumers' daily needs at affordable prices. The existence of modern retail that mushroomed like a large market caused competition to threaten the existence of traditional retail. More and more large markets are also taking advantage of the era of technology and social media so that they are involved as online markets. The onslaught of the times and the advancement of modern retail has caused grocery stalls that are friendly to the community to be threatened. Although it varies in order to meet the needs of the community, it certainly creates negative and positive sides, especially for grocery stalls so that it requires various strategies to survive and develop at this time.